The other Black girl [book club bag] - Harris, Zakiya Dalila (Bloomsbury Publishing, 2022)
Twenty-six-year-old editorial assistant Nella Rogers is tired of being the only Black employee at Wagner Books. Fed up with the isolation and the micro-aggressions, she's thrilled when Hazel starts working in the cubicle beside hers. They've only just started comparing natural hair care regimens, though, when a string of uncomfortable events cause Nella to become Public Enemy Number One and Hazel, the Office Darling. Then the notes begin to appear on Nella's desk: LEAVE WAGNER. NOW. It's hard to believe Hazel is behind these hostile messages. But as Nella starts to spiral and obsess over the sinister forces at play, she soon realises that there is a lot more at stake than her career.